Nanoparticle targeting at cells - de la Fuente, Jesus M (Langmuir : the ACS journal of surfaces and colloids, 2006)
Gold nanoparticles have been used for analytical and biomedical purposes for many years. In fact, the labeling of targeting molecules with nanoparticles has revolutionized the visualization of cellular or tissue components by electron microscopy. We report in this study the derivatization of tiopronin-protected nanoparticles with ethylenediamine and poly(ethylene glycol) bis(3-aminopropyl) terminated and their functionalization with the GRGDSP peptide sequence by a straightforward and economical methodology. The particles were subsequently tested in vitro with a human fibroblast cell line to determine the biocompatibility, and the cell-particle interactions, using fluorescence and scanning electron microscopies. The results indicate that tiopronin gold nanoparticles aggregate due to culture medium proteins, whereas the tiopronin gold nanoparticles derivatized with ethylenediamine induce endocytosis, and the same nanoparticles derivatized with poly(ethylene glycol) derivative promote particle-cell adhesion